Allelopathic effect of cissus cactiformis extract on seed germination and seedling growth of lettuce - Sebola, Makoena Flora (My University, 2014)
Following the withdrawal of synthetic pesticides from agro-chemical markets, several extracts from various plants have been tested. Despite this progress, some plant extracts with bio-pesticidal properties have also been documented for their phytotoxic properties. This study was conducted to investigate allelochemical content of Cissus cactiformis plant. Also, to determine its allelopathic effect based on the presence of the phytochemical components on seed germination and seedling growth of lettuce. Phytochemical analysis of C. cactiformis plant extract showed differences in the allelochemical components of different extracts tested. Saponins, terpenoids, flavonoids, tannins, alkaloids, coumarins, phytosterols were detected in plant materials extracted using acetone, methanol and ethanol. With these extracts the presence of phenolic compounds and cardiac glycoside were not detected. However, in distilled water extract terpenoids, flavonoids, tannins, alkaloids, coumarins and phenolic compounds were detected, with saponins and cardiac glycoside being absent. Lettuce seeds in germination bioassay were exposed to four treatments, viz. 0, 0.5, 1.0 and 1.25mg/mℓ of the different extract laid-out in a completely randomised design replicated four times. In all variables measured, treatments were significantly (P ≤ 0.01) different for acetone, ethanol, distilled water and methanol extract of C. cactiformis plant. Mean germination percentage, hypocotyl and radicle length for control were highest when compared to other levels of each extract type. Similarly seedling growth bioassay comprised of six treatments, viz. 0, 0.5, 1.0, 1.25, 2.0 and 2.25 g extracts of C. cactiformis plant per pot, arranged in a randomised complete design, with six replicates in the greenhouse. All measured variables were not significant at P ≤ 0.05 which showed no variation. The results revealed that irrespective of the solvents used, extract of C. cactiformis plant had allelopathic effects on the seed germination whereas no effect was observed on seedling growth of lettuce which makes C. cactiformis plant possible to be adapted as alternative post-emergent bio-nematicide without affecting the growth of other crops.
Thesis (M.Sc. (Plant Production)) -- University of Limpopo, 2014
Keywords: Lettuce seeds; phytochemical; terpenoids; Lettuce; Allelopathy; Plant growing media